2016
DOI: 10.1016/j.phymed.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of bradykinin B2 and muscarinic receptors in the prolonged diuretic and antihypertensive properties of Echinodorus grandiflorus (Cham. & Schltdl.) Micheli

Abstract: Our results suggest that the mechanisms through which Echinodorus grandiflorus extracts induce prolonged diuresis and reduce blood pressure in normotensive and 2K1C rats are mainly related to activation of muscarinic and bradykinin receptors with direct effects on prostaglandins and nitric oxide pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
0
23
0
7
Order By: Relevance
“…[3,4] Owing to the therapeutic importance of diuretic drugs for pathological conditions of fluid and electrolyte overload, the investigation for new options that are capable of increasing urinary volume excretion as well as electrolytes (particularly sodium) is extremely relevant. In this field, the products derived from medicinal plants, as recently shown in several scientific researches, remain as an alternative source for the obtaining of extracts [5][6][7][8][9][10][11] and the isolation of compounds [12][13][14][15][16] with potential applicability for usage as diuretic agents. Conversely, the antidiuretic activity of natural products has also been described in experimental trials, which plant extracts or fractions may have a dual role on renal function depending on the dose used, [17][18][19][20] highlighting the importance of multidose assays, as well as special attention in future therapeutic approaches with these specific types of herbal preparations.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Owing to the therapeutic importance of diuretic drugs for pathological conditions of fluid and electrolyte overload, the investigation for new options that are capable of increasing urinary volume excretion as well as electrolytes (particularly sodium) is extremely relevant. In this field, the products derived from medicinal plants, as recently shown in several scientific researches, remain as an alternative source for the obtaining of extracts [5][6][7][8][9][10][11] and the isolation of compounds [12][13][14][15][16] with potential applicability for usage as diuretic agents. Conversely, the antidiuretic activity of natural products has also been described in experimental trials, which plant extracts or fractions may have a dual role on renal function depending on the dose used, [17][18][19][20] highlighting the importance of multidose assays, as well as special attention in future therapeutic approaches with these specific types of herbal preparations.…”
Section: Introductionmentioning
confidence: 99%
“…Statins also inhibit oxidative stress-induced endothelial senescence [41]. Further support for the potential of ESEG as a viable alternative cardiological therapy derives from the fact that it has diuretic and antihypertensive activity [20] in addition to cardioprotective effects that were similar to simvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of different classes of secondary metabolites, including alkaloids, tannins, terpenoids, and saponins, has drawn attention [15,18]. However, polyphenolic compounds, including tannins, flavonoids, and C-glycosides, are worth mentioning because of their diuretic and antihypertensive effects [19,20]. Recent pharmacological studies have shown that different preparations that are obtained from E. grandiflorus have diuretic [19,20], antiedematous [18], anti-inflammatory [21,22], antihypertensive [20,23], and vasodilatory [24] effects, making the species a potential new candidate for herbal medicines.…”
Section: Heart-protective Effects Of Echinodorus Grandiflorus In Rabbmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, a number of medicinal plant species have been described in folk medicine due to their effects on the cardiovascular system [8]. Among them, the leaves of Echinodorus grandiflorus (Cham & Schltdl) Micheli (Alismataceae) have been used in infusion and decoction preparations as anti-inflammatory [9], diuretic [10], and hypotensive agents [11,12] in different regions of the country. Due to its long history of popular use in rural communities, information on the medicinal benefits of this plant and its chemical and morphological characteristics were described in the 5th edition of the Brazilian Pharmacopoeia [13].…”
Section: Microvascular Effects Of Echinodorus Grandiflorus On Cardiovmentioning
confidence: 99%